2016
DOI: 10.2174/1570161114666161007164510
|View full text |Cite
|
Sign up to set email alerts
|

Link between Metabolic Syndrome and Insulin Resistance

Abstract: Metabolic syndrome (MetS) is a leading public health and clinical challenge worldwide. MetS represents a group of interrelated risk factors that predict cardiovascular diseases (CVD) and diabetes mellitus (DM). Its prevalence ranges between 10 and 84%, depending on the geographic region, urban or rural environment, individual demographic characteristics of the population studied (sex, age, racial and ethnic origin), as well as the criteria used to define MetS. Persons with MetS have higher mortality rate when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
131
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(136 citation statements)
references
References 0 publications
1
131
0
4
Order By: Relevance
“…This finding may be an alert for screening clinical features used to detect early risk of developing metabolic syndrome. Considering criteria based on insulin resistance, and supported by waist circumference data, MetS prevalence ranges between 10 and 84% worldwide, depending on the geographic region, urban or rural environment, individual demographic characteristics of the population studied (gender, age, racial, and ethnic origin), and the criteria used to define MetS (24). At baseline, BMI was higher in adult-onset GH deficiency, but both groups presented a high percentage of fat mass, suggesting that there is a negative repercussion of GH deficiency in body composition (25).…”
Section: Discussionmentioning
confidence: 99%
“…This finding may be an alert for screening clinical features used to detect early risk of developing metabolic syndrome. Considering criteria based on insulin resistance, and supported by waist circumference data, MetS prevalence ranges between 10 and 84% worldwide, depending on the geographic region, urban or rural environment, individual demographic characteristics of the population studied (gender, age, racial, and ethnic origin), and the criteria used to define MetS (24). At baseline, BMI was higher in adult-onset GH deficiency, but both groups presented a high percentage of fat mass, suggesting that there is a negative repercussion of GH deficiency in body composition (25).…”
Section: Discussionmentioning
confidence: 99%
“…There are several possible mechanisms which can explain the relationship between hypothyroidism and NAFLD. First, obvious relations between hypothyroidism and metabolic changes have been reported, which include IR, dyslipidemia and obesity and they have important roles in the development of NAFLD ( 54 , 55 ). Both IR and obesity are vital factors in the development of NAFLD, which are also common in hypothyroidism patients compared to those general population ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, Demir et al found that hypothyroidism can cause NAFLD in rat models, and pointed out that obesity is one of the key factors in the relationship between hypothyroidism and NAFLD ( 29 ). The metabolic changes aforesaid among hypothyroidism patients can thus further result in the development of NAFLD ( 54 , 55 ). Second, thyroid hormones can regulate lipid metabolism in the liver via thyroid hormone receptor β, and they can decrease cholesterol and triglyceride levels ( 58 60 ).…”
Section: Discussionmentioning
confidence: 99%
“…Evident relations amongst hypothyroidism and metabolic changes have been accounted for, which incorporate IR, dyslipidemia and weight and they have imperative parts in the advancement of NAFLD. 28 Even though hypothyroidism is allied with mechanisms of metabolic syndrome and NAFLD is reflected as the hepatic manifestation of metabolic syndrome, while there are numerous reasonable mechanisms that could clarify this conceivable relation, the present study, which included all published observational studies, found a strong epidemiological evidence association between NAFLD and hypothyroidism. Leptin is considered as one of the explanations of this association because it is found to be increased in patients with hypothyroidism and it is also found to be higher in NAFLD as it can promote hepatic insulin resistance and be involved in hepatic fibrogenesis.…”
Section: Discussionmentioning
confidence: 49%